Pathogenic Fungal Species Associated with Digestive System of Periplaneta americana (Blattaria: Blattidae) Trapped from Residential Dwellings in Ahvaz City, Southwestern Iran - Hamid Kassiri; Majid Zarrin; Rahele Veys-Behbahani (Tehran University of Medical Sciences, 2018)
Background: Cockroaches are the most prevalent domestic pests of a worldwide distribution. They were recognized as possible vectors of pathogenic bacteria, viruses, fungi and parasites in residential dwellings and hospital environments. The present study isolated and identified yeasts and filamentous fungi from digestive tract of American cockroaches, collected from three different residential regions of Iran. Methods: Seventy cockroaches were sampled using direct collection (hand catch), vacuum cleaner and sticky traps in Ahvaz, Iran in 2009-2010. Their medically important fungal microorganisms were isolated from digestive tract using standard mycological methods. Filamentous fungi were identified by macroscopic and microscopic examination. Yeasts were identified by API ID32C-32100 kit. Results: A high percentage of cockroaches (88.6%) were detected to carry fungi of medical importance. Overall, 23 fungi species/genera were isolated from the American cockroaches' alimentary tract. The fungi isolated from cockroaches, from the residential regions were species of Aspergillus, Rhizopus, Penicillium, Mucorales, Alternaria, Cladosporium, Mycelia, Chrysosporium, Candida, Rhodotorula, Zygosaccharomyces, and Debaryomyces. Candida spp. (41.4%), Aspergillus spp. (37.1%) and Rhodotorula spp (27.1%) were the most common fungi recovered on cockroaches. Candida albicans and Candida glabrata were the commonest species of the genus Candida. In addition, Aspergillus niger and A. flavus were the most frequent species of the genus Aspergillus. Conclusion: American cockroaches may carry pathogenic fungi in the urban areas of Ahvaz.